2016
DOI: 10.1111/hdi.12465
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of delivered dialysate sodium concentration

Abstract: Background The results of studies investigating the effects of hyponatraemic dialysates have been mixed, with some reporting positive effects including reduction in blood pressure and inter-dialytic weight gains, whereas others have not been able to demonstrate any effect. These studies assume that setting a lower dialysate sodium results in the delivery of a hyponatraemic dialysate. We therefore measured delivered sodium to determine reliability. Methods We measured dialysate sodium in 10 BBraun Dialog+ and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…shows higher dialysate sodium in Gambro machines compared to Fresenius machines (with the same set value). Similar results were recently reported by Ekbal et al [14], who found higher dialysate sodium in the Dialog dialysis machine of B. Braun compared to 4008 type of Fresenius. Approximately 3-4 mmol/L higher dialysate sodium in Gambro machines compared to 5008 Fresenius and DBB05 of Nikkiso were also seen by Descombes et al [3].…”
Section: Other Technical Reasons For Dialysate Sodium Variationssupporting
confidence: 91%
“…shows higher dialysate sodium in Gambro machines compared to Fresenius machines (with the same set value). Similar results were recently reported by Ekbal et al [14], who found higher dialysate sodium in the Dialog dialysis machine of B. Braun compared to 4008 type of Fresenius. Approximately 3-4 mmol/L higher dialysate sodium in Gambro machines compared to 5008 Fresenius and DBB05 of Nikkiso were also seen by Descombes et al [3].…”
Section: Other Technical Reasons For Dialysate Sodium Variationssupporting
confidence: 91%
“…There may also be a discrepancy between prescribed dialysate sodium concentration and that delivered. The reported discrepancies are ±2 mmol/L up to +7 mmol/L, with higher prescribed dialysate sodium concentrations associated with greater differences . Finally, the Gibbs‐Donnan effect also impacts sodium diffusion across the dialyzer membrane .…”
Section: Discussionmentioning
confidence: 99%
“…The reported discrepancies are 62 mmol/ L up to 17 mmol/L, with higher prescribed dialysate sodium concentrations associated with greater differences. 7,8 Finally, the Gibbs-Donnan effect also impacts sodium diffusion across the dialyzer membrane. 6 This effect results from the formation of an electro-chemical boundary on the blood side of the dialyzer composed of negatively charged proteins and accompanying cations.…”
Section: Discussionmentioning
confidence: 99%
“…The exact point where dialysate sodium would result in a net zero diffusive transport of sodium during dialysis is affected by Donnan equilibrium, as well as the relation of plasma water sodium to plasma sodium level. Also, dialysis solution sodium used in these analyses was the nominal level, and the nominal level has been shown to be different from the measured value [21]. However, the HEMO Study dataset included patients in whom either large positive or large negative sodium gradients were present and there was no detectable impact of a sodium gradient on the magnitude of the increase in serum total protein concentration during dialysis relative to the calculated change in total body water.…”
Section: Discussionmentioning
confidence: 99%